Key issues in childhood and youth studies - Kassem, Derek; Murphy, Lisa, 1969-; Taylor, Elizabeth, 1970- (Routledge, 2010)
Explores a range of key issues related to children and childhood, from birth to eighteen years. This book is suitable for students as well as those studying relevant professional qualifications in social work, teaching and health.